Pengaruh Penerapan E-Government Terhadap Pelaksanaan Good Governance Di Dinas Komunikasi Informatika Dan Statistik Kabupaten Wajo - Muammar, M Ahmar; Parawu, Hafiz Elfiansya; Nasrulhaq, Nasrulhaq (Universitas Muhammadiyah Makassar, 2021)
The objectives of this research is to find out the effect of controlling to the employee work professionalism at Statistic Center Agency in Pinrang Regency. The type of research used is the measurement of quantitative and objective statistics. The population in this research were 23 people and used as a sample. The file collection techniques are using observation, documentation and cousionary techniques against the response. The identity of respondents was seen from gender, age, religion, and level of education. The result of this research indicated that the influence of the controlling to the employee work professionalism at Statistic Center Agency in Pinrang Regency means that it has a positive and significant effect on employee work professionalism. The result of this research have been tested using a simple regression tool with a positive result of 1,948 and a significant level of 0,000 smaller than 0,05 with the R square value of 0,997 or 99,7 % which means the controlling contribution to employee work professionalism at Statistic Center Agency in Pinrang Regency, while 3% is affected by other variables not examined in this research such as motivation, work experience, etc.